Od pridobivanja do sanacije - Buzina, Lara (Javna uprava, 2023)
Mining is one of the most important economic activities supplying society with mineral resources. Mining is becoming less important in Slovenia due to the scarcity of ores and the growing role of cleaner and renewable energy sources. When the above-mentioned mine closures began in Slovenia, concerns arose about the rehabilitation of mining areas and their (lack of ) legal regulation. The path to the implementation of mine rehabilitation in Slovenia is rather administrative and bureaucratic. To carry out the remediation, several permits need to be obtained, as well as an arduous documentation process, which is frequently the cause of the lengthy remediation process. Another impediment to the effective implementation of rehabilitation is the fragmentation of ownership of the mining areas and the holders of the mining rights.
Keywords: energija; energy; mineral raw materials; mineralne surovine; mining; mining areas; reclamation; rudarstvo; sanacija